2003
DOI: 10.1002/ijc.11463
|View full text |Cite
|
Sign up to set email alerts
|

Freshly isolated bone marrow cells induce death of various carcinoma cell lines

Abstract: In some carcinomas such as digestive tract carcinomas, bone marrow infiltration by tumor cells is a frequent event but usually remains a micrometastatic disease and rarely induces overt bone lesions. The mechanisms responsible for the control of these metastases in the bone marrow remain poorly known. We show that freshly isolated bone marrow cells from human, murine and rat origin rapidly kill a wide range of syngeneic or xenogeneic carcinoma cell lines in culture. Further analysis of this cytotoxic process i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 29 publications
(44 reference statements)
1
20
0
Order By: Relevance
“…Nearly simultaneous with the discovery that NO was EDRF, independently Hibbs and coworkers showed that NO was the active factor in the macrophage mediated killing of tumor cells in model systems 1 . Research in the area of NO mediated killing of tumor cells by macrophages has continued since the early observations, and as anticipated, observations since then have demonstrated that the processes and cell biology involved is more complex than originally conceived 2 . This area will not be covered in this review.…”
Section: Introduction and Overviewmentioning
confidence: 83%
“…Nearly simultaneous with the discovery that NO was EDRF, independently Hibbs and coworkers showed that NO was the active factor in the macrophage mediated killing of tumor cells in model systems 1 . Research in the area of NO mediated killing of tumor cells by macrophages has continued since the early observations, and as anticipated, observations since then have demonstrated that the processes and cell biology involved is more complex than originally conceived 2 . This area will not be covered in this review.…”
Section: Introduction and Overviewmentioning
confidence: 83%
“…Tumor cells that are detected molecularly in the LN of patients with NSCLC are subjected to one of three fates: death, dormancy, or proliferation [18]. Most metastatic cells die in this hostile microenvironment [19,20], or they balance the growth rates with the death rates [21]. Other cells adapt by responding to stimuli from the microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, multiple stem cells engineered to express anticancer genes at a specific tumor locus, have been reported to effectively suppress tumors (1,4,11,14,17,(22)(23)(24)(25)(26)(27). However, certain reports have shown that non-engineered native stem cells have an inherent ability to inhibit the growth of several types of cancer cells (28,29). However, the use of engineered stem cells can help solve unexpected problems associated with transfected genes, such as mutation, inappropriate insertion into genomic DNA and viral vector virulence.…”
Section: A B a Bmentioning
confidence: 99%